The relativistic glass transition: A thought experiment - Collin J. Wilkinson; Karan Doss; Greg Palmer; John C. Mauro (Journal of Non-Crystalline Solids: X, 2019)
In order to quantify the temporal effects on the glass transition at relativistic speeds, the Deborah number is analyzed incorporating the Maxwell relation for relaxation time. Using the time dilation coefficient proposed by Einstein for special relativity, the new observation times are calculated, and the corresponding shear modulus is used to determine the shift in the glass transition temperature. The new glass transition temperature is incorporated into the MYEGA expression to estimate the relativistic viscosity curve. B2O3 glass is used as an example to show the impact of relativistic time scales on viscosity and the glass transition. Keywords: Glass transition, Relativity, Viscosity